Rural science education during and beyond COVID-19: teachers’ strategies and prospects from a Philippine perspective - Aldea, Kristian Q.; Dayawon, Marites A. (Institute of Advanced Engineering and Science, 2025)
Distance learning during the COVID-19 pandemic challenged many aspects of the teaching and learning process. However, challenges with the virtual classes were arguably more intense in the rural areas of developing countries, considering technological and socio-geographic limitations. We argue that despite these limitations, rural areas provide opportunities (rural affordances), which may enhance teaching strategies. With the aim of expounding this perspective, we explored science teachers’ strategies derived from rural affordances (SDRA) and drawn teachers’ perceptions of learners’ engagement after the strategies’ intervention. Based on the results, three types of SDRA were utilized, namely: contextualization of educational materials for science activities (CEMSA), integration of citizen science in science activities (ICSSA), and integration of traditional knowledge in science activities (ITraKSA), wherein a significant learner engagement with the SDRA are perceived by teachers after the SDRA intervention. Prospects for the utilization of the strategies in post pandemic settings suggest their potential roles in future distance learning schemes as well as in face-to-face learning modality. A paradigm that outlines educational intervention may assimilate the advantages of the SDRA in science teaching. Science education may further communications with policy-makers and stakeholders for a curriculum that drives synergism between rural teaching strategies responsive to pedagogical limitations.